Plantain squirrel callosciurus notatus in a plantation habitat - Mohd Noor, Hafidzi (Universiti Putra Malaysia Press, 1998)
The daily activity pattern or actogram of four Callosciurus notatus in a mixed plantation crop of oil palm and cacao under coconut in Peninsula-r Malaysia was determined by using radiotelemetry. Resulls suggest that C. notatus exhibits a daily activity pattern from 0630 to 1730 with several peaks. Two major peaks are identified, one at day break (abollt 0730) and another before midday (about 1130). The two peaks were followed by a relative ressation of activity in the afternoon (1430 - 1630). a third smaller peak was recorded in the evening (1730). Individual valiation exists as one individual showed four small peaks interspersed by short periods of rest. The multiple peaks may -reflect the foraging strategy in meeting specific dietary needs. A survey of stomach contents suggests that insects constitute the preferred item in the first couple of hours and a mixed diet of insects and plant matter later during the day.